Progress on the Mechanisms and Neuroprotective Benefits of Dexmedetomidine in Brain Diseases - Zhenxing Tao; Pengpeng Li; Xudong Zhao (Brain and Behavior)
ABSTRACT Introduction Dexmedetomidine, a highly specific α2 agonist, has been extensively utilized in clinical sedation and surgical anesthesia since its introduction in 2000 due to its excellent sympatholytic, sedative, and analgesic effects. This review aimed to identify new approaches for the treatment of patients with brain disorders by thoroughly describing the mechanism of action of dexmedetomidine and examining its neuroprotective effects from the standpoints of basic and clinical research. Methods The PubMed and Web of Science databases were searched using the keywords dexmedetomidine and related brain diseases, although relevant articles from the last decade were included for detailed summarization and analysis. Results Dexmedetomidine has shown strong neuroprotective effects, such as protection of the blood‐brain barrier, decreased neuronal death, maintained hemodynamic stability, and reduced postoperative agitation and cognitive dysfunction. Furthermore, dexmedetomidine has been shown to exert various neuroprotective effects, including anti‐inflammatory and antioxidative stress effects, modulation of autophagy, and reduction of apoptosis in cerebral diseases. Conclusions Dexmedetomidine acts as a neuroprotective agent against brain diseases during all phases of treatment. However, clinical trials with larger sample sizes are required to optimize dosage and dosing strategies.